Readability of Questionnaires Assessing Listening Difficulties Associated With (Central) Auditory Processing Disorders. - Atcherson, Samuel R.; Richburg, Cynthia M.; Zraick, Richard I.; George, Cassandra M. (Language, Speech & Hearing Services in Schools, 2013)
Purpose: Eight English-language, student- or parent proxy-administered questionnaires for (central) auditory processing disorders, or (C)APD, were analyzed for readability. For student questionnaires, readability levels were checked against the approximate reading grade levels by intended administration age per the questionnaires' developers. For proxy questionnaires, results were compared to the reading grade level for the average U.S. adult and the minimum 5th- to 6th-grade reading level for health materials as recommended by adult health literacy experts. Method: This was a descriptive study that was based on the results of a commercially available readability calculations software package. Text-based files of the 8 questionnaires were analyzed using 3 readability formulas: FORCAST (Caylor & Sticht, 1973), Flesch Reading Ease (FRE; Flesch, 1948), and Gunning's Fog index (FOG; Gunning, 1952). Results: The FORCAST formula, the most appropriate for nonnarrative-type materials, indicated that all 8 questionnaires were written at reading levels between the 8th and 10th grades. The FRE and FOG formulas, designed for narrative-type materials, were generally in good agreement with one another but varied widely between the upper 4th- and 12th-grade levels. Conclusion: In an effort to decrease respondent burden, developers should consider readability as another testable psychometric construct. Clinicians should take into account the functional health literacy skills of adult proxy respondents when giving self-administered questionnaires.